STRATEGI PEMASARAN PRODUK PADA MEGA MART SUNGALIAT DI TINJAU DARI KUALITAS PELAYANAN, FASILITAS DAN HARGA TERHADAP KEPUASAN KONSUMEN - Yanto Yanto (JEM Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the product marketing strategy carried out by Mega Mart Sungaliat in terms of perceptions of service quality, facilities, and prices on consumer satisfaction. The conclusion of this research is that there is an effect of perceived service quality, facilities, and prices on consumer satisfaction either simultaneously or partially. Suggestions from this research are that mega mart Sungaliat in increasing customer satisfaction needs to pay attention to the problem of available facilities such as air conditioners which often experience damage or jams, improving service quality often gives a smile, and the price management should increase product value on condition value indicators. which has the lowest value in the minds of consumers.